ChemInform Abstract: Crystal Structure, Energy Band and Optical Properties of Dysprosium Monophosphate DyPO4. Issue 48 (2nd December 2014) - Khadraoui, Z.; Bouzidi, C.; Horchani‐Naifer, K.; Ferid, M.
Abstract Single crystals of DyPO4 are prepared by high temperature solid state reaction of a 1:20 mixture of Dy2O3 and NH4H2PO4 (1273 K, 1 d; controlled cooling).